Vobling - vocabulário bilíngue de linguística, português-inglês, direcionado por corpus - Yamamoto, Márcio Issamu (2020)
In this thesis we developed the prototype of a Bilingual Vocabulary in the fields of Linguistics, named VoBLing (in Portuguese) available at http://vobling.votec.ileel.ufu.br/. This research was conducted in Portuguese and in English, based on comparable corpus, and made it available on VoTec - Online Technical Vocabulary (FROMM, 2007, 2018) platform available on the internet, for free access. The theories that support this research are those of Barbosa (1990), on the concept of Vocabulary; Cabré (1999), on the Communicative Theory of Terminology, henceforth TCT; Finatto (2001a), Krieger and Finatto (2004) and Barros (2004), on Terminology in relation to the elaboration of entry definitions. As a methodology and also as a theory, we adopted Corpus Linguistics (BERBER SARDINHA, 2004, 2009; MCENERY; HARDIE, 2012; SCOTT, 2016; 2020) and VoTec as terminology platform parameters (FROMM, 2007). The texts that comprise the corpora used as source for data extraction to choose the terms and definition constructions are specialized, written, subdivided into two different types in Linguistics: (1) PhD theses, master’s dissertations and scientific articles; and (2) Linguistics manuals and Linguistics collections. Part of these texts were compiled by undergraduate students, graduate students and by this researcher, in disciplines taught by Professor Fromm, and as part of the methodological step of this research. The manuals were compiled by the researcher, that is, the digitalization of manuals in Portuguese (LP), the compilation of manuals in English (LI) from the internet and, finally, the availability of these materials in txt files. Data were processed by the software package of Wordsmith Tools 7.0 and 8.0 (SCOTT, 2016, 2020), using its Wordlist, keyword list, and concordance tools. The original proposal of the domain tree of Linguistics is by Fromm (2008), updated by Fromm and Yamamoto (2020), comprising 47 subdomains. The organization of distinctive features on VoBLing was based on Frame Semantics, by Fillmore (1975; 1976; 2003 and 2005), Souza (2019) and on Frame-based Terminology, according to Faber Benítez et al. (2005). As a result, VoBLing provides 200 bilingual entries that include key terms from the field of Linguistics, Descriptive Linguistics, Applied Linguistics, and its subfields.